Response of Some Sunflower (Helianthus annuusL) Hybrid Cultivars as Influenced by Argel (Solenostemmaargel, Del. Hayne) and Nitrogen Under Irrigation in Sudan - H. M. Adam Abubaker; Adam Hassam Mohamed Abdalla; M. A. Magid Faiza; Eldeen Z. Abakar Bahar; M. A. Mohamed Mohamed; A. M. Al badawi Annas (Journal of Agronomy Research, 2020)
A field experiment was conducted during 2017/2018 to assess the effects of Argel (Solenostemmaargel, Del. Hayne) and Nitrogen fertilizer on the performance of two Sunflower Hybrid cultivars, with the objectives to exploit an easy, economic, and accessible organic fertilizer, the Argel in the phase of the continuous increasing prices of chemical fertilizers.. This experiment was laid out on spilt-split-plot experiment in Randomized Complete Block Design (RCBD) with four replications. Observations were taken on some agronomic traits (Plant height (m), Leaf area (LA), leaf Number (NL), Leaf Area Index (LAI) and Mean Seed Weight). The results revealed that the application of Argel and Nitrogen fertilizer have significantly increased the leaf Area (F= 7.22, P < 0.001), Plant Height (F=2.68, P < 0.2001), Leaf Number (F= 3.90, P < 0.0024), Leaf Area Index (F= 3.83, P < 0.0026) and Mean Seed Weight of both Serena and Opera cultivars respectively compared to the control. However, the different treatments of Argel and Nitrogen reflected variable degree of increase for the studied parameters. The study concludes that Argel is very promising, therefore a further study with different levels of Argel including other plant parameters is recommended.
Keywords: Leaf Area Index